2011
DOI: 10.1007/s11695-011-0479-x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Clinical Trial of Laparoscopic Roux-en-Y Gastric Bypass Versus Laparoscopic Sleeve Gastrectomy for the Management of Patients with BMI < 50 kg/m2

Abstract: LSG and LRYGB are equally safe and effective in the amelioration of comorbidities, while LSG is associated with fewer postoperative metabolic deficiencies, without the need of supplementation. Furthermore, LSG is a promising bariatric procedure, equally effective to LRYGB at 3 years follow up on weight reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
197
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 308 publications
(214 citation statements)
references
References 46 publications
11
197
0
6
Order By: Relevance
“…The initial search identified 581 publications, of which 576 were excluded, leaving 5 publications for analysis. [14][15][16][17][18] One study, 19 which was the subset of another study, 14 was excluded; another study 20 was the republication of the trial by Woelnerhanssen and colleagues 15 and was also excluded. The 5 trials of LRYGB and LSG for morbid obesity or T2DM with a total of 396 patients that we included in our analysis were retrieved from the electronic databases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The initial search identified 581 publications, of which 576 were excluded, leaving 5 publications for analysis. [14][15][16][17][18] One study, 19 which was the subset of another study, 14 was excluded; another study 20 was the republication of the trial by Woelnerhanssen and colleagues 15 and was also excluded. The 5 trials of LRYGB and LSG for morbid obesity or T2DM with a total of 396 patients that we included in our analysis were retrieved from the electronic databases.…”
Section: Discussionmentioning
confidence: 99%
“…Three trials 14,17,18 reported the remission of T2DM, which was much better in the LRYGB group than in the LSG group. The meta-analysis revealed a significant difference between the 2 groups (OR 9.08, 95% CI 2.39-34.41, p = 0.001; Fig.…”
Section: Remission Of T2dmmentioning
confidence: 99%
“…But LSG is not complication-free at all and one of the major postoperative complication is still the staple line leak, which occurs in approximately 2.2-2.4% of patients [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. There are various factors which influence the risk of leak.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays it has been accepted as a definitive stand-alone procedure due to the excellent results in terms of excess weight loss (%EWL) and control of comorbidities, with significant 3 and 5-year experiences that justify this recommendation [5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Since its introduction in 2007, SG case volumes have increased dramatically, with published weight loss results comparable to RYGB. SG is considered a restrictive procedure; however, it has been increasingly recognized to have metabolic effects similar to those observed after RYGB (21). A recent 5-year outcomes study has reported successful SG results, with an 86% average EWL (22).…”
Section: Weight Lossmentioning
confidence: 99%